Efeitos da irrigação na sobrevivência, transpiração e no teor relative de água na folha em mudas de Eucalyptus grandis em diferentes substratos - Lopes, Jane Luísa Wadas [UNESP]; Amaral Guerrini, Iraê [UNESP]; Saad, João Carlos Cury [UNESP]; Silva, Magali Ribeiro da [UNESP] (My University, 2005)
This work it to asses the irrigation depths effects in survival degree, in transpiration and relative water content in the leaf in seedlings of Eucalyptus grandis produced in substratum different and spaced at 49 cm 2. The work was developed at Camará Forest Seedling, in Ibaté, SP, from winter 2003 to spring 2003 and were made of a factorial 5 × 4, with four repetitions, where 5 means, the number of daily watering (6, 8, 10, 12 and 14 mm), applied several times (at 10 am, 13 pm and 16 pm), and 4 means the number of substratum (FB - fiber of coconut; CATV - barks of tree, peat and vermiculita; CPV - barks of pinus and vermiculita and MIX - 70 % of CPV and 30 % of FB). Three times (at 24, 37 and 42 days after irrigation depths) and at 108 days after sowing were assessed transpiration, relative water content in the leaf. The results pointed out that the watering irrigation depths as well as the substratum in characteristics assessed. The survival degree was strongly influenced by the watering irrigation depths: i.e. irrigation depths of 6 and 8 mm height drastically compromised the production. As to physiological characteristics, it can be observed that the higher depths enhanced relative water content in the leaf values, thus, it turns out in a good correlation between the watering depths height and this parameter; the transpiration statistically did not present any difference as the irrigation depths changed in any substratum, but for every substratum happened that the transpiration rate in the plant increased as the lamina height increased depending on the substratum physical. Thus, it can be concluded that the watering laminas as high as 14 mm day -1 and FB and MIX to warrant this better results for parameters of interest.
Irrigation effects on survival, transpiration and on relative water content in the leaf of seedlings of Eucalyptus grandis in different substrates
Keywords: Eucalyptus; Irrigation; Seedling; Substratum; Survival degree; Transpiration; Irrigation depths; Leaf values; Correlation methods; Parameter estimation; Seed; Water; Forestry; Correlation; Moisture Content; Parameters; Seedlings